Topological quantum field theory and polynomial identities for graphs on the torus - Fendley, Paul; Krushkal, Vyacheslav (arXiv.org, 2020)
We establish a relation between the trace evaluation in SO(3) topological quantum field theory and evaluations of a topological Tutte polynomial. As an application, a generalization of the Tutte golden identity is proved for graphs on the torus.